Escalating interventional recanalization therapy in non-cirrhotic, non-malignant acute portal vein thrombosis. Issue 12 (December 2019) - Gerwing, Mirjam; Wilms, Christian; Heinzow, Hauke; Sporns, Peter B.; Heindel, Walter; Schmidt, Hartmut; Wildgruber, Moritz; Köhler, Michael
Abstract : Objective: To evaluate the effectiveness of interventional therapy in acute, non-malignant, non-cirrhotic portal vein thrombosis. Methods: We present a retrospective study of eight consecutive patients who presented with an acute non-malignant, non-cirrhotic portal vein thrombosis and were treated by mechanical recanalization using an escalating scheme including local aspiration, thrombolysis, rheolysis and the implantation of transjugular intrahepatic portosystemic shunt or other visceral stents. Results: Recanalization rates applying the escalating scheme were good, with a success rate of 75%. However, major complications occurred in 50% of patients, mostly due to bleeding at the percutaneous access site, and minor complications in 12.5% of patients. Conclusion: Interventional therapy is effective in acute portal vein thrombosis, but should only be performed at specialized centers and based on an individual treatment decision.